Health Care Access for Adults With Intellectual and Developmental Disabilities: A Scoping Review. (October 2017) - Williamson, Heather J.; Contreras, Graciela M.; Rodriguez, Erica S.; Smith, Jennifer M.; Perkins, Elizabeth A.
Adults with intellectual and/or developmental disabilities (IDD) often experience health disparities. To address disparities, Healthy People 2020 includes specific disability and health goals focused on improving health care access. The study's purpose was to review the literature exploring health care access for adults with IDD to identify opportunities for occupational therapy research and practice. A scoping review was completed of articles discussing health care access among adults with IDD in the United States. Thirty-seven articles met the inclusion criteria. Results are framed using the ecology of human performance theory identifying person and environmental issues affecting health care access of adults with IDD. Opportunities exist for occupational therapy to improve participation and health of adults with IDD through engaging in research and practice efforts addressing health care access. Occupational therapy could develop interventions to establish skills and abilities and recommend changes to the health care environment.